The experience of regulating retail Forex in the foreign jurisdictions - A. A. Dulyov (Путеводитель предпринимателя, 2020)
The article deals with foreign jurisdictions on the subject of regulation of the retail Forex market. The analysis of the activity of the state agencies for the stable functioning of the OTC Forex market is carried out.